Experimental evidence for multiple controls on fault stability and rupture dynamics - Mei, Cheng (2022)
The stability of frictional sliding affects the spectrum of fault slip, from slow-slip events to earthquakes. In laboratory experiments, the transition from stable sliding to stick-slip is often explained by the ratio of the stiffness of the loading system to a critical value that depends on effective normal stress and other physical properties. However, theoretical considerations indicate other controls on fault stability that have not been validated experimentally. Here, we exploit the dependence of frictional properties on load-point velocity to explore the dynamics of frictional sliding with gradual variations of frictional properties. We use the period-multiplying and chaotic cycles that appear at the transition between stick-slip and stable sliding as a sensitive indicator of fault stability. In addition to the stiffness ratio, we find that the ratio of the parameters that describe the dependence on velocity and state constitutes another control on the stability of faulting and rupture dynamics. Variations of these two non-dimensional parameters among faults may help explain the wide range of rupture styles and recurrence patterns observed in nature.